Economic Marginalisation and Political Struggles of Historical Antecedents of Banditry in Nigeria and Their Reflection in the Fourth Republic, from 1999 to 2023 - Irabor, Paul (Studia Historiae Oeconomicae, 2025)
Banditry has deep roots in Nigeria's precolonial and colonial history, which became evident in the Fourth Republic. This study used published data to trace the history of banditry in Nigeria and examine its manifestation under various administrations in the Fourth Republic, from 1999 to 2023. The findings showed that economic marginalisation by the privileged few and political struggles among the elites were key factors in the historical origins of banditry in Nigeria’s precolonial and colonial periods. These historical factors continued to influence banditry during the Fourth Republic, as seen in patterns under different administrations, such as the Niger Delta militant activities during Obasanjo’s era over the marginalisation of oil-producing communities, Boko Haram insurgency during Yar' Adua’s tenure due to the poor socioeconomic conditions in the north-east, herder-farmer conflicts under Goodluck’s government over resource disputes related to scarce arable land for cattle grazing and farming, and secessionist armed groups during Buhari’s administration over political marginalisation of the south-eastern region from the national mainstream.